ENT 530 Social Media Portfolio: Gadget Gen-Z / Mohamad Zakaria Zainol - Zainol, Mohamad Zakaria (2021)
“Warming Your Ears with Wireless Music” is a tagline for Gadget Gen Z as we offer a good quality of wireless earphones with affordable price to all our customers. The main objective of the business is to give the customers feel the different between wireless earphones and the normal earphones by offer variety and comfortable wireless earphones to our customer. We started our online business on March 30, 2021, through the social media platform. Our targeted customers are the millennial audiophiles or any kind of person that enjoy good quality sound and are technologically interested. According to the customers’ feedbacks, our wireless earphones gave them a fantastic quality of sounds. They also can answer calls without the need to pick up their phone. Also, it is very easy to work out while listening to music and to make it short, using wireless earbuds is convenient. As for now, Gadget Gen Z owned by Mohamad Zakaria Bin Zainol and run by Mohamad Zakaria Bin Zainol and helps from his business partner, Muhammad Rashdan Bin Rosli. The business only used social media platforms to promote and advertise all the products. For example, Gadget Gen Z has Facebook page to attract, engage and spread the awareness of this useful wireless earphones to the customers. We offered cash on delivery service and customers who are not in the coverage area, they can choose to get the products by postage or courier services.